Light disturbance with multifocal contact lens and monovision for presbyopia - Fernandes, Paulo RB (2018)
Dysphotopsia affects a significant number of patients, particularly after visual correction with multifocal optical designs. Purpose Evaluate light distortion (LD) in two modalities of contact lens (CL) wear: multifocal (MF) and monofocal (MV). Methods This was a randomized, double-masked, crossover study involving 20 presbyopic patients. Patients were randomized first into either MF or MV for 15 days of use with a 1 week wash-out period between each lens type. The LD was evaluated with the Light Distortion Analyzer (LDA, University of Minho) under monocular and binocular conditions. The light distortion index (LDI, %), among other parameters were analyzed. Subjective quality of vision was assessed with the Quality of Vision (QoV). Results The LD showed an increase in all parameters in both CL modalities being significant for MV in the non-dominant eye (p < 0.030, for all LD parameters). For the MF, there was also a significant increase in LDI (p = 0.016) and in BFCrad (p = 0.022) in the non-dominant eye. After 15 days of MF lens wear, there was a significant decrease in all LD parameters (p < 0.002) in the dominant eye. Binocularly, a significant improvement from 1 to 15 days was observed for LDI (p = 0.009) and BFCrad (p = 0.0013) with MF. The QoV questionnaire showed no significant changes with neither CL. Conclusions. Adaptation to light disturbances induced by MF CL is more effective compared to MV. Practitioners will have greater success if they prepare their patients for the adaptation required as their vision will get better and have less of an issue with light disturbance